DIGITAL CULTURAL RESOURCES IN LEARNING COMMONS: A STUDY WITH REFERENCE TO ASSAM - Anurag Borpatra Gohain, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Learning Commons has become an important topic in the literature of Library and Information Sciences. This paper tries emulating a feasibility aspect of digital cultural resources of Assam as a component of virtual Learning Commons.